2012
DOI: 10.1111/j.1523-5378.2011.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of AlbuMAX II® as a Blood or Serum Alternative for the Culture of Helicobacter pylori

Abstract: AlbuMAX II(®) (Gibco BRL) can be used as a serum/blood replacement for the cultivation of H. pylori in solid and liquid media. This medium could be useful for an improved understanding of H. pylori metabolism or for antigen production. Furthermore, AlbuMAX II(®) (Gibco BRL) may be suitable for use in remote locations, particularly in areas where frozen storage of serum may be a problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…The study of Hutton et al demonstrated the growth of H. pylori in solid and liquid media containing a highly purified, lipid-rich bovine serum albumin called Albu-MAX II ® (Gibco BRL, Grand Island, NY, USA). Growth was comparable to the growth obtained on blood agar or liquid media with serum and higher than on media containing b-cyclodextrin [36]. The effect of another compound, cholesterol, as a substitute for serum or cyclodextrin, was demonstrated to be a valuable option for the supplementation of media for the H. pylori growth [37].…”
Section: Culturementioning
confidence: 63%
“…The study of Hutton et al demonstrated the growth of H. pylori in solid and liquid media containing a highly purified, lipid-rich bovine serum albumin called Albu-MAX II ® (Gibco BRL, Grand Island, NY, USA). Growth was comparable to the growth obtained on blood agar or liquid media with serum and higher than on media containing b-cyclodextrin [36]. The effect of another compound, cholesterol, as a substitute for serum or cyclodextrin, was demonstrated to be a valuable option for the supplementation of media for the H. pylori growth [37].…”
Section: Culturementioning
confidence: 63%
“…Η χρησιμοποίηση ορού ή αίματος ζώων (π.χ. αίμα αλόγου ή προβάτου) είναι δυνατή αλλά η χρήση ανθρώπινου αίματος φαίνεται να προσδίδει ένα επιπλέον πλεονέκτημα[112]. Μείγμα αντιβιοτικών το οποίο ανέπτυξαν οι Dent και συν.…”
unclassified